Legacies and new obstacles for an inclusive water governance: the California experience - de Oliveira , Alberto (Espacio Abierto, 2021)
Scholars from different political approaches argue that governance may harmonize antagonistic interests. However, governance’s concept is still imprecise, and it has been used in a contradictory way. This paper’s aim is to discuss governance limitations to overcome obstacles regarding land monopolization and water ‘commoditization’. Through California experience, this paper shows how historic legacies have reinforced changes in commodity market, narrowing the margin of maneuver of vulnerable households. Inclusive governance may be the best shot to reduce inequalities regarding water access, but it is not a magical solution. There is a long way to follow and political fights still must happen.